The (bio)diversity of science reflects the interests of society. Issue 8 (1st October 2007) - Wilson, John RU; Procheş, Şerban; Braschler, Brigitte; Dixon, Edd S.; Richardson, David M.
Abstract : For ecologists to develop robust generalizations and principles, a broad taxonomic and geographic spread of research is required, but, in practice, most generalizations are based on the research of individual scientists and groups, and their choice of study organism is affected by many different factors. We analyzed researchers' choice to assess potential biases. In particular, by comparing the relative representation of species in the scientific literature and on the Internet, we explored how the choice of study organism is influenced by societal interests. While there is a strong positive correlation between output in the scientific literature and on the web, deviations from this general pattern suggest that, when compared with societal biases, research agendas are more directly influenced by economic priorities and practical limitations, and less by geographical and sociopolitical barriers. Although the range of biological research reflects the needs of society, there are still large taxonomic and geographic gaps. By focusing on specific groups, we are developing an in‐depth knowledge of certain taxa, but if ecologists are to develop generalizations, we may need to widen our research scope.